PERSEPSI PENTINGNYA PROMOSI KESEHATAN UNTUK MENINGKATKAN KESADARAN ERGONOMI KERJA PADA PETUGAS CLEANING SERVICE DI LINGKUNGAN KAMPUS - Bunga Nurjannah Gea; Ade Risma; Munanda Andin; Alya Dwi Ananta; Suci Aulia Ramadan S; Zuhrina Aidha; Sabrina Cahyati Nst (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Due to less ergonomic work postures, cleaning service workers are prone to musculoskeletal disorders. This study explores cleaning service workers' perceptions of the importance of health promotion and increasing awareness of work ergonomics in campus environments. A qualitative approach was used to obtain data through in-depth interviews with one informant who had worked for six years. The results showed that, although the informant had basic knowledge of proper posture, fatigue and work pressure impaired its application. Common complaints include back, shoulder, and knee pain, which are generally treated with traditional methods. Informants also expressed the need for continuous training and educational materials, such as posters. Health promotion was important in raising awareness of work ergonomics and preventing long-term health risks.